Estudo de sequestrantes de H2S em petróleo do Estado do Espírito Santo - Portela, Natália de Aquino (2011)
The presence of contaminant compounds in the crude oil is a challenge for petroleum industry, and diverse and comprehensive the problems caused by the presence of compounds such as sulfur, especially H2S. The consequences affect human health, environmental and economic damage. Petroleum companies use various methods of removal of this gas, and injecting a H2S scavenger it’s a actual alternative treatment. In order to exhibit such problems and the variety of commercial products and procedures in order to eliminate or reduce the sulfur content in the crude oil, it is essential to the study treatment for the removal of H2S in the crude oil, and the need for attention greater in choice of products scavenger H2S with the feasibility of laboratory scale tests. Through laboratory studies, can plan improvements that will be applied to production, such as choosing more efficient products. Therefore, this study aimed to test the efficiency of capture of H2S by compositions of H2S scavengers, list some properties of these products, such as density, dynamic viscosity, pH, electrical conductivity, color and infrared spectrum with the corresponding efficiency capture of the sulfide. It was observed that some properties of scavengers, such as electrical conductivity and density does not correlate with the sulfide content capture the scavenger in the crude oil. Was traced out on a profile of scavenger that have been most effective for the proposed tests, both in capturing the sulfide content, which have been sequestering the most basic and viscous residue and the amount of sulfur remaining in the oil after a process of washing were the triazine-based scavengers. Was used, as well tool multivariate analysis on data from the infrared H2S scavengers intervals which were found in the spectrum where the scavenger having bands best correlates these ranges that characterize types of common bonding in the formulations of scavengers